2021
DOI: 10.1002/smll.202006730
|View full text |Cite
|
Sign up to set email alerts
|

Ni/Mo Bimetallic‐Oxide‐Derived Heterointerface‐Rich Sulfide Nanosheets with Co‐Doping for Efficient Alkaline Hydrogen Evolution by Boosting Volmer Reaction

Abstract: Molybdenum disulfide (MoS2) is a promising alternative to Pt‐based catalysts for electrocatalytic hydrogen evolution reaction (HER) in an acidic environment. However, alkaline HER activity for molybdenum disulfide is limited by its slow water dissociation kinetics. Interface engineering is an effective strategy for the design of alkaline HER catalysts. However, the restricted heterointerfaces of current catalysts have significantly limited their alkaline HER performance. Herein, a novel assembly of cobalt‐dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 60 publications
0
69
0
Order By: Relevance
“…The slow kinetic process of alkaline HER could be ameliorated by heterostructure interface engineering through tune the adsorption energy between the catalyst and intermediate of the alkaline HER process. [102][103][104] The different components of the heterostructure catalyst play synergic roles in alkaline HER will be discussed in this section, including promoting the water dissociation in the Volmer process as well as the followed hydrogen generation process.…”
Section: Synergistic Heterostructure For Hydrogen Evolution Reactionmentioning
confidence: 99%
“…The slow kinetic process of alkaline HER could be ameliorated by heterostructure interface engineering through tune the adsorption energy between the catalyst and intermediate of the alkaline HER process. [102][103][104] The different components of the heterostructure catalyst play synergic roles in alkaline HER will be discussed in this section, including promoting the water dissociation in the Volmer process as well as the followed hydrogen generation process.…”
Section: Synergistic Heterostructure For Hydrogen Evolution Reactionmentioning
confidence: 99%
“…+ OH − . 49,50 As marked in blue, the water dissociation reaction (TS-1) on Co@CoO proceeded with much lower energy barrier (0.52 eV) than that on Co (0.88 eV). This suggested that the O-abundant surface CoO site was more favorable for cleavage of H–OH on Co site (TS-1 step in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] In order to overcome the above-mentioned problems, many methodologies have been proposed, such as increasing the exposure of active edge sites, 20,21 introducing vacancies or defects, [22][23][24] atomic doping, [25][26][27] crystalline phase regulation, [28][29][30] and construction of a heterostructure. [31][32][33][34] Among the above strategies, the construction of heterostructures has been proven to be a feasible strategy for improving the HER activity of MoS 2 . Bao et al synthesized a Co-Ni-P/MoS 2 heterostructure through the in situ growth of MoS 2 on MOFsderived Co-Ni-P spheres, which provided abundant active sites and showed an excellent overall water splitting performance under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%